Do schiff bases-based urease inhibitors improve plant growth and affect the activity of soil arginase? - Chaves-Silva, Samuel; Horta, Lívia P.; Souza, Leandro T.; da Silva, Cleiton M.; Dohanik, Caroline S.; Goulart, Gisele A.C.; Marriel, Ivanildo E.; de Fátima, Ângelo; Modolo, Luzia V. (Industrial crops and products, 2020)
[Display omitted] •Three Schiff bases were found to be 31 % more potent than NBPT on soil ureases.•The Schiff bases are not detrimental to the germination and plant development.•Schiff base 4 stimulated carbon allocation from millet roots to shoots.•Schiff base 5 induced the elongation of lettuce roots by 31 % compared to control.•Urea coated with Schiff base 5 yielded 37.5 % more nitrogen in millet shoots. The increase in nitrogen (N) use efficiency in acidic soils is necessary to boost the tropical agriculture yields and mitigate N losses and the supplementation of urea-based fertilizers with urease inhibitors has been used as a strategy to overcome such problems. Here, 12 Schiff bases were synthesized to investigate the extent of their ability to inhibit ureases and some effects on plant development and soil microbiota metabolism. The performance of compounds 4, 5 and 7 on ureases present in an agricultural clayey dystrophic Red Latosol was greater than that of N-(butyl) thiophosphoric triamide (NBPT), an inhibitor reference. Compound 5 was the most potent on soil ureases; Its concentration necessary to inhibit the soil ureases by 50 % (IC50) was 27.5 μM, while the IC50 values for 4 and 7 were respectively 129 and 233.9 μM. Phytotoxicity assays showed that 4, 5 or 7 are not harmful to Lactuca sativa L. (lettuce; dicot) or Pennisetum glaucum (L.) R. Br. (pearl millet; monot) and 4 and 5 (both at 100 μM) even improved the elongation of lettuce roots. Further tests performed on the pearl millet-clayey dystrophic Red Latosol system revealed that urea coated with 5 (1.0 % w/w) was as efficient as NBPT-coated urea (0.25 or 0.5 % w/w), yielding 37.5 % (on average) more N in millet shoots in comparison to plants cultivated in the presence of urea only. Strikingly, the Schiff base 5 did not impair the activity of soil arginases from day 2 to day 7 after soil supplementation with urea plus compound 5. The inhibitory effect of Schiff base 5 and NBPT on soil ureases was transient since the soil urease activity in samples exposed to urea plus 5 or NBPT was similar to that of urea-treated soils from day 2 and so on. Overall, the Schiff base 5 (and 4 and 7 as well) are promising additive candidates for further studies toward the development of new urea-based fertilizer formulations.